Intrinsically motivating employees' online knowledge sharing: Understanding the effects of job design. Issue 6 (December 2015) - Pee, L.G.; Lee, J.
Highlights Job characteristics influence intrinsic motivation through affective commitment. Skill variety has an n-shaped curvilinear effect. Job autonomy, task feedback, and task significance have a positive linear effect. Managers can intrinsically motivate employees' knowledge sharing through job design.